Maternal Metabolic Biomarkers are Associated with Obesity and Excess Gestational Weight Gain - Antony, Kathleen M.; Romezi, Mona; Lindgren, Kourtnee; Mitchell, Kristen B.; Venable, Susan F.; Racusin, Diana A.; Suter, Melissa A.; Aagaard, Kjersti M. (American Journal of Perinatology, 2020)
Objective The purpose of this study was to evaluate the independent contribution of maternal obesity and gestational weight gain (GWG) in excess of the Institute of Medicine's guidelines on levels of maternal serum inflammatory and metabolic measures.Study Design Banked maternal serum samples from 120 subjects with documented prepregnancy or first trimester body mass index (BMI) were utilized for analyte analyses. Validated, BMI-specific formulas were utilized to categorize GWG as either insufficient, at goal or excess based on the Institute of Medicine guidelines with gestational age adjustments. Serum was analyzed for known inflammatory or metabolic pathway intermediates using the Luminex xMap system with the MILLIPLEX Human Metabolic Hormone Magnetic Bead Panel. Measured analytes included interleukin-6, monocyte chemoattractant protein-1, and tumor necrosis factor-α and metabolic markers amylin, c-peptide, ghrelin, gastric inhibitory polypeptide, glucagon-like peptide-1, glucagon, insulin, leptin, pancreatic polypeptide, and peptide YY. Kruskal–Wallis ANOVA and Pearson's correlation coefficients were calculated for each marker.Results C-peptide, insulin, and leptin all varied significantly with both obesity and GWG while glucagon-like peptide-1 varied by BMI but not GWG. These analytes covaried with other metabolic analytes, but not with inflammatory analytes.Conclusion Maternal metabolic biomarkers at delivery vary significantly with both obesity and GWG. Taken together, these findings suggest that GWG (with and without comorbid obesity) is an important mediator of measurable metabolites in pregnancy but is not necessarily accompanied by inflammatory measures in serum. These findings are consistent with GWG being an independent risk factor for metabolic disturbances during pregnancy.
Keywords: pregnancy; obesity; gestational weight gain; metabolic markers; inflammatory markers